Influence of User Generated Content on Purchase Intention in Bandung City - Vianita Sopandi; Dani Dagustani (Pustaka Bangsa Indonesia, 2026)
This study aims to analyze the influence of User Generated Content (UGC) on Purchase Intention with Brand Image as a mediating variable for Brand A serum products among Generation Z in Bandung City. The research employs a quantitative approach using descriptive and verificative methods. Data were collected from 100 respondents who had used or never used Brand A serum products, obtained through a questionnaire. Data analysis was conducted using Partial Least Square – Structural Equation Modeling (PLS-SEM) to examine both direct and indirect effects among variables. The results indicate that User Generated Content has a positive and significant effect on Brand Image, and Brand Image also has a positive and significant effect on Purchase Intention. Furthermore, Brand Image is proven to mediate the relationship between User Generated Content and Purchase Intention.